Extent and drivers of vegetation type conversion in Southern California chaparral. Issue 7 (1st July 2019) - Syphard, Alexandra D.; Brennan, Teresa J.; Keeley, Jon E.
Abstract: The native chaparral shrublands of Southern California support exceptional biodiversity and provide critical ecological services, but increased fire frequency threatens to extirpate much of the chaparral due to long regeneration times needed between fires for many species. When short fire intervals inhibit shrub recovery, this favors invasion of exotic herbaceous species, and vegetation type conversion from woody shrubs to grassland is therefore a serious ecological concern in this biodiversity hotspot. Despite a history of field studies documenting the detrimental effect of short‐interval fire, the extent of vegetation type conversion and the conditions under which it occurs have not been documented at a landscape scale. Our objective was thus to provide an unbiased assessment of how and how much vegetation type conversion is occurring in Southern California chaparral. We used a chronosequence of aerial photographs to quantify percentage woody and herbaceous cover change from 1953 to 2016 across randomly sampled plots in San Diego County, then related conversion and decline to a range of explanatory variables including fire, proximity to human disturbance, and biophysical landscape characteristics. Within the 63‐yr study period, there was substantial net woody cover loss, and in the plots that were initially more than 75% woody cover in 1953, 59% experienced a decline, with a mean woody cover loss of 22.5%. Of these, 28% heavily type‐converted to the point that herbaceous vegetation covered more than 50% of the plot. The top drivers for woody conversion and decline included a fire interval shorter than 15 yr and total number of fires, actual evapotranspiration, and elevation. Although human land use variables were not strong independent contributors to either chaparral conversion or decline, 26% of the initial vegetated plots were directly converted to development or other human disturbance types. The combination of direct habitat loss and unintentional vegetation type conversion represents a substantial ecological impact in Southern California that can have far‐reaching impacts via loss of ecological services and by increasing the flammability of the landscape in general. Efforts to reduce fire frequency will be key to preventing further losses.